Combining magnetic particle imaging and magnetic fluid hyperthermia in a theranostic platform. (5th April 2017) - Hensley, Daniel; Tay, Zhi Wei; Dhavalikar, Rohan; Zheng, Bo; Goodwill, Patrick; Rinaldi, Carlos; Conolly, Steven
Abstract: Magnetic particle imaging (MPI) is a rapidly developing molecular and cellular imaging modality. Magnetic fluid hyperthermia (MFH) is a promising therapeutic approach where magnetic nanoparticles are used as a conduit for targeted energy deposition, such as in hyperthermia induction and drug delivery. The physics germane to and exploited by MPI and MFH are similar, and the same particles can be used effectively for both. Consequently, the method of signal localization through the use of gradient fields in MPI can also be used to spatially localize MFH, allowing for spatially selective heating deep in the body and generally providing greater control and flexibility in MFH. Furthermore, MPI and MFH may be integrated together in a single device for simultaneous MPI–MFH and seamless switching between imaging and therapeutic modes. Here we show simulation and experimental work quantifying the extent of spatial localization of MFH using MPI systems: we report the first combined MPI–MFH system and demonstrate on-demand selective heating of nanoparticle samples separated by only 3 mm (up to 0.4 °C s −1 heating rates and 150 W g −1 SAR deposition). We also show experimental data for MPI performed at a typical MFH frequency and show preliminary simultaneous MPI–MFH experimental data.